Urban‐rural disparities in childhood obesogenic environments in the United States: Application of differing rural definitions. Issue 1 (30th May 2022) - Wende, Marilyn E.; Meyer, M. Renée Umstattd; Abildso, Christiaan G.; Davis, Kara; Kaczynski, Andrew T.
Abstract: Background: Research is needed that identifies environmental resource disparities and applies multiple rural definitions. Therefore, this study aims to examine urban‐rural differences in food and physical activity (PA) environment resource availability by applying several commonly used rural definitions. We also examine differences in resource availability within urban‐rural categories that are typically aggregated. Methods: Six food environment variables (access to grocery/superstores, farmers' markets, fast food, full‐service restaurants, convenience stores, and breastfeeding‐friendly facilities) and 4 PA environment variables (access to exercise opportunities and schools, walkability, and violent crimes) were included in the childhood obesogenic environment index (COEI). Total COEI, PA environment, and food environment index scores were generated by calculating the average percentile for related variables. US Department of Agriculture Urban Influence Codes, Office of Management and Budget codes, Rural‐Urban Continuum Codes, Census Bureau Population Estimates for percent rural, and Rural Urban Commuting Area Codes were used. One‐way ANOVA was used to detect urban‐rural differences. Results: The greatest urban‐rural disparities in COEI ( F =310.2, P <.0001) and PA environment ( F =562.5, P <.0001) were seen using RUCC codes. For food environments, the greatest urban‐rural disparities were seen using Census Bureau percent rural categories (food: F =24.9, P <.0001). Comparing remote rural categories, differences were seen for food environments ( F =3.1, P =.0270) and PA environments ( F =10.2, P <.0001). Comparing metro‐adjacent rural categories, differences were seen for PA environment ( F =4.7, P =.0090). Conclusion: Findings inform future research on urban and rural environments by outlining major differences between urban‐rural classifications in identifying disparities in access to health‐promoting resources.